Decomposition of tetracycline in aqueous solution by corona discharge plasma combined with a Bi2MoO6 nanocatalyst. Issue 12 (17th September 2014) - He, Dong; Sun, Yabing; Li, Shunbin; Feng, Jingwei
Abstract BACKGROUND A new method of tetracycline (TC) degradation by corona discharge plasma with a suspended Bi2MoO6 catalyst was investigated. The flake‐like structure particles were successfully synthesized by a solvent‐thermal method and analyzed by XRD, SEM, TEM, BET and XRF. The catalytic activity, the reaction mechanisms, the intermediates of TC degradation and the proposed pathway were also evaluated for the reaction process. RESULT The removal rate of 250 mL TC with 50 mg L−1 was enhanced from 62% to 96% in 24 min with the addition of Bi2MoO6 in the range 0–1.5 g L−1, under a discharge input power of 36.0 W. The corresponding removal rate of TOC increased from 25% to 61%, and 95% of the catalyst (1.0 g L−1) was settled in 60 min. CONCLUTIONS It was shown that a synergistic effect existed between corona discharge plasma and Bi2MoO6 in the process of TC degradation. The intermediates and a possible degradation pathway of TC were determined based on LC‐MS analysis. The study proposes an efficient technology and degradation mechanism for TC wastewater treatment. © 2014 Society of Chemical Industry